Indicators Relevant for Energy Security Risk Assessment of Critical Energy Infrastructure - Mladenovska, D., Lazarevska A. M. (My University, 2017)
Energy security is one of the most important issues affecting not only national economies, but as well the national security systems. Hence, various approaches in different studies and reports are utilized to analyze this topic. Energy systems are subject to diverse risks and threats which can vary according to specific geopolitical circumstances, geographical location, technical failures, environmental risks, social crises and timescale. Any source of danger to the continuity of the energy production, its consumption and/or final supply or other energy services is defined as a risk to the national energy security and integrity. This topic is even more important when it comes to energy infrastructure defined as critical, which can often be subject to asymmetrical risks and threats. Bearing in mind the long history of war and conflicts, as well as recent refugees crises, the region of South East Europe, in particular the Western Balkans is quite vulnerable regarding those issues. In order to protect the energy system and to ensure its security, it is necessary to understand the causes of danger, the nature of risks, as well as to quantify their impact. Thus, identifying tangible and measurable indicators represents a sound basis towards tackling risks and preparing measures for response and mitigating consequences.
Keywords: Energy security; Critical energy infrastructure; Risk assessment; Asymmetrical threats